The Good, the Bad, and the Ordinary: Anti-Social Behavior in Profit and Non-Profit Organizations - Emmanuelle Auriol; Stefanie Brilon (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Intrinsic motivation of workers may arise from different individual motives. While some workers care about the mission of an organization and derive an intrinsic benefit from advancing this mission ("good" workers), others derive pleasure from some form of destructive or anti-social behavior ("bad" workers). We show that mission-oriented organizations can take advantage of the intrinsic motivation of good workers. Compared to profit-oriented organizations, lower bonus payments and lower monitoring are necessary in order to achieve a high output. However, as soon as there are bad workers, mission-oriented organizations may become more vulnerable to their anti-social behavior than profit-oriented organizations. We analyze the optimal wage contracts and monitoring levels for both types of organization and discuss appropriate measures of ex ante candidate screening to overcome the problems caused by bad workers.
Keywords: D21; D23; L31; 330; motivated agents; non-profit; sabotage; candidate selection